SAMPLE SIZE AND LINEAR RELATIONS IN TRAITS OF CUT AND GRAZING SORGHUM - CARGNELUTTI FILHO, ALBERTO; BUBANS, VALÉRIA ESCAIO; FILLIPIN OSMARI, LUCAS; MANFIO SOMAVILLA, FELIPE; MORENA ORTIZ, VITHÓRIA (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
The objectives of this work were to determine the sample size (number of plants) needed to estimate the mean of cut and grazing sorghum (Sorghum bicolor (L.) Moench), Nutribem cultivar, traits and investigate the linear relations among traits. At 86 days after sowing, 110 plants of sorghum were selected at random. The traits evaluated for each plant were: plant height, stem diameter, number of nodes, number of leaves, leaf fresh matter, stem fresh matter, shoot fresh matter, leaf dry matter, stem dry matter, and shoot dry matter. The sample size was determined to estimate the means of the traits, assuming estimation errors equal to 1% (higher precision), 2%, ..., and 20% (lower precision) of the mean. Scatter plots, correlation analysis, and path analysis investigated the relationship among traits. Fourteen plants were needed to estimate the means of plant height, stem diameter, number of nodes, and number of cut and grazing sorghum leaves, with a maximum error of 10% of the mean and a 95% confidence level. With the same precision, to estimate the means of leaf, stem, and shoot fresh and dry matter, 48 plants are needed. Plant height positively correlates with stem and shoots fresh and dry matter. The number of leaves has a positive linear relation with leaf fresh and dry matter.